2022
DOI: 10.3389/fnhum.2022.924845
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being and cognitive aging in Black, Native American, and White Alzheimer’s Disease Research Center participants

Abstract: Psychological well-being is associated with cognition in later life but has not been examined across diverse populations—including minoritized communities at disproportionately high risk of dementia. Further, most previous work has not been able to examine links between specific facets of psychological well-being and performance within distinct cognitive domains that can capture subclinical impairment. Using a well-characterized sample followed through enrollment in an NIH-funded Alzheimer’s Disease Center, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In a study of 84 healthy adults aged 35 -64, eudaimonic well-being was associated with downregulated CTRA gene expression, while hedonic well-being was associated with CTRA upregulation. 30 Wyman and colleagues 34 recently reported on the association between psychological wellbeing as measured in the NIH Toolbox on Emotion and found that, in a race-stratified analysis, Black and American Indian/Alaskan Native participants reported lower life satisfaction than White participants, but similar scores on positive affect, meaning in life, and purpose in life. Measures of executive functions, but not episodic memory, were higher in those with higher life satisfaction scores.…”
Section: Discussion -1522 Need To Remove 22 Words…mentioning
confidence: 99%
“…In a study of 84 healthy adults aged 35 -64, eudaimonic well-being was associated with downregulated CTRA gene expression, while hedonic well-being was associated with CTRA upregulation. 30 Wyman and colleagues 34 recently reported on the association between psychological wellbeing as measured in the NIH Toolbox on Emotion and found that, in a race-stratified analysis, Black and American Indian/Alaskan Native participants reported lower life satisfaction than White participants, but similar scores on positive affect, meaning in life, and purpose in life. Measures of executive functions, but not episodic memory, were higher in those with higher life satisfaction scores.…”
Section: Discussion -1522 Need To Remove 22 Words…mentioning
confidence: 99%